2009
DOI: 10.1002/pro.194
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of α‐synuclein in an aggregation prone state

Abstract: The relation of a-synuclein (aS) aggregation to Parkinson's disease has long been recognized, but the pathogenic species and its molecular properties have yet to be identified. To obtain insight into the properties of aS in an aggregation-prone state, we studied the structural properties of aS at acidic pH using NMR spectroscopy and computation. NMR demonstrated that aS remains natively unfolded at lower pH, but secondary structure propensities were changed in proximity to acidic residues. The ensemble of conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
113
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(137 citation statements)
references
References 29 publications
22
113
2
Order By: Relevance
“…Dedmon et al showed strong interactions between the highly charged C terminus and the NAC region (33). Cho et al showed that compaction increased between the C terminus and the NAC at low pH and the C terminus became more rigid, a similar conclusion to our finding that diffusion slows (6). Recently Trexler and Rhoades measured various intramolecular distances by single molecule FRET and showed substantial collapse at low pH but the effect was largest for the C terminus (34).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Dedmon et al showed strong interactions between the highly charged C terminus and the NAC region (33). Cho et al showed that compaction increased between the C terminus and the NAC at low pH and the C terminus became more rigid, a similar conclusion to our finding that diffusion slows (6). Recently Trexler and Rhoades measured various intramolecular distances by single molecule FRET and showed substantial collapse at low pH but the effect was largest for the C terminus (34).…”
Section: Discussionsupporting
confidence: 89%
“…In vitro, the aggregation propensity of α-synuclein is very sensitive to solution conditions such as temperature, pH, salt concentration, and solution cofactors. There has been significant work to discover the structures that form in association with lipids, structures of final aggregates, and structures that may be the aggregation precursor (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, the underlying reason for why monomeric α-synuclein is so prone to aggregation is still unknown.…”
mentioning
confidence: 99%
“…Both SEC and native gels separate proteins based on molecular size and shape, and our findings illustrate a key physical feature of disordered proteins-that they are significantly more extended than globular proteins of the same MW. This has been shown to be true for disordered monomer AS by several different experimental methods, 7,8 including native gel electrophoresis. 9 Moreover, it emphasizes that caution must be used in interpreting molecular size from methods that are dependent upon the shape of the molecules measured.…”
Section: Resultsmentioning
confidence: 79%
“…However, all evidence indicates that the aggregation pathway passes through an at least partially unstructured state. Thus, much work has focused on which subset of the conformation ensemble is prone to nucleating aggregation (3)(4)(5)(6).…”
mentioning
confidence: 99%